2016
DOI: 10.2344/15-00012.1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Profile and Patient Satisfaction After Ambulatory Anesthesia for Dental Treatment—A Crossover Comparison Between Propofol and Sevoflurane

Abstract: The purpose of this study was to determine which anesthetic was preferable for ambulatory anesthesia: propofol alone or sevoflurane alone. A crossover study was performed to compare the recovery profile and patient satisfaction after 2 anesthesia methods. Twenty healthy patients with severe anxiety toward dental treatment undergoing 2 sessions of day-case dental treatment received either propofol or sevoflurane anesthesia. The order of these methods was randomized. The depths of anesthesia were kept constant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The reason being, sevoflurane gets rapidly eliminated after it is stopped as seen from blood-gas distribution coefficient of 0.69 and moreover there is 50% decrease in anaesthetic concentration of sevoflurane in less than 5 mins irrespective of duration of anaesthesia. 13 Similar results were observed by Singh et al and Ohkushi et al 9,16 Rapid recovery and psychological immaturity has been considered as a reason for emergence delirium following sevoflurane anaesthesia. 17 At just before extubation, significant number of patients were restless (RASS:1), 81% in sevoflurane group and 46.96% in propofol group (p value<0.001).…”
Section: Discussionsupporting
confidence: 59%
“…The reason being, sevoflurane gets rapidly eliminated after it is stopped as seen from blood-gas distribution coefficient of 0.69 and moreover there is 50% decrease in anaesthetic concentration of sevoflurane in less than 5 mins irrespective of duration of anaesthesia. 13 Similar results were observed by Singh et al and Ohkushi et al 9,16 Rapid recovery and psychological immaturity has been considered as a reason for emergence delirium following sevoflurane anaesthesia. 17 At just before extubation, significant number of patients were restless (RASS:1), 81% in sevoflurane group and 46.96% in propofol group (p value<0.001).…”
Section: Discussionsupporting
confidence: 59%
“…According to a study carried out in 2016 by Keita Ohkushi et al, also compared these two agents and they found that the mean extubation time in Sevoflurane anaesthesia was tend to be shorter than propofol anaesthesia and they assessed it in terms of seconds and it was noted to be as 920 ± 537 seconds with propofol as compared to 595 ± 186 seconds managed with Sevoflurane with a P value of 0.016. 13 A. Sultan, H. B. Ali, S. Ashraf et al P J M H S Vol. 16, No.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed in a different types of surgery or which had utilized different tools to estimate anesthetic consumption, had different results compared with our study. [10][11][12][13] As previously explained, the residual effect of midazolam and fentanyl used during induction might affect the recovery profile.…”
Section: Sevoflurane and Tci Propofol Recovery Timementioning
confidence: 96%